The Scent of Stress: Evidence From the Unique Fragrance of Agarwood - Naziz, Pearlin Shabna; Das, Runima; Sen, Supriyo (Frontiers in Plant Science, 2019)
Agarwood (Aquilaria spp.) fragrance and its origin in stress make it probably the most suitable model to study stress-induced aroma. Production being confined only to certain small pockets of South and Southeast Asia, agarwood is arguably the costliest wood in the world. Formation of fragrant agarwood resin is the outcome of complex biotic, abiotic and physical stress on the Aquilaria trees. The intricate mechanism by which some 150 odd fragrant molecules that constitute agarwood aroma is formed is still not clearly understood. The present review, therefore, aims to bring to focus this less known but highly valuable stress-induced aroma from Asia. Discussions on agarwood species, occurrence, distribution, formation, products have been included as a foundation. Although global trade in agarwood and its products is estimated at 6-8 billion USD, no reliable data is readily available in literature. Therefore, an effort has been made to review the current status of agarwood trade. The element of stress and its correlation to agarwood aroma is discussed in the subsequent sections. Natural agarwood formation as well as technologies and interventions in agarwood induction are stress-based (natural and artificial injury, insect and fungal attack, chemical induction). The molecular triggers are gradually coming to light as new studies are implicating jasmonate, LOX signalling and other stress reaction routes as the source of agarwood aroma. This review. therefore, has strived to compile the information which is scattered across scientific as well as other authentic literature and update the reader on the current status. More information about the specific roles of other vital stressors like insects, abiotic and genetic factors is eagerly awaited from ongoing and future research to further understand the unique fragrance of agarwood.